JENIS - JENIS PERENCANAAN PENDIDIKAN - Riswandha Ipnu Nawawi; Saifullah; Rochmat Widodo; Nelma Elpayuni; Junaidah; Abdurrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Educational planning is a systematic effort to achieve the desired educational goals, and can be divided into several types based on scale, time and specific goals. Types of educational planning include strategic, operational, curriculum and financing planning. Strategic planning focuses on achieving the long-term vision of the education system, taking into account external and internal factors that can influence the direction of national education. Meanwhile, operational planning is more practical and oriented towards the implementation of daily educational activities at the institutional level. Curriculum planning focuses on developing and structuring teaching materials to meet learning needs in line with current developments and job market demands. Financing planning involves managing resources to support the sustainability of planned educational programs. Each type of planning is interrelated and has an important role in creating an education system that is effective, efficient and responsive to change. This article will review in more depth the characteristics of each type of educational planning, the challenges faced in its implementation, as well as recommendations for strengthening integration between types of planning in order to achieve better educational goals.